2015
DOI: 10.1109/tmc.2014.2362753
|View full text |Cite
|
Sign up to set email alerts
|

CWC: A Distributed Computing Infrastructure Using Smartphones

Abstract: Every night, many smartphones are plugged into a power source for recharging the battery. Given the increasing computing capabilities of smartphones, these idle phones constitute a sizeable computing infrastructure. Therefore, for an enterprise which supplies its employees with smartphones, we argue that a computing infrastructure that leverages idle smartphones being charged overnight is an energy-efficient and cost-effective alternative to running certain tasks on traditional servers. While parallel executio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…Overnight charges A recent study investigating of battery charges of 15 participants over 3 weeks [2] reported that charges during the day and over night vary dramatically in length, with charges between 10pm and 5am having a median duration of 7 hours while other charges had a median duration of 30 minutes. Our dataset supports their findings, with a median AC charge duration of 5 hours 10 minutes (4 hours for AC and USB combined) for the above definition of overnight charges and a 33 minute median for charges during the day, irrespective of charge type.…”
Section: Energy Managementmentioning
confidence: 99%
“…Overnight charges A recent study investigating of battery charges of 15 participants over 3 weeks [2] reported that charges during the day and over night vary dramatically in length, with charges between 10pm and 5am having a median duration of 7 hours while other charges had a median duration of 30 minutes. Our dataset supports their findings, with a median AC charge duration of 5 hours 10 minutes (4 hours for AC and USB combined) for the above definition of overnight charges and a 33 minute median for charges during the day, irrespective of charge type.…”
Section: Energy Managementmentioning
confidence: 99%
“…They enforced an execution setting for automaton that permits for running desktop Java applications on smart phones in an automatic fashion also created similar observations about scheduling tasks based on processing capabilities of smart phones [1].…”
Section: Existing and Proposed Systemmentioning
confidence: 99%
“…To overcome this problem the solution is using smart phones when they are being charged at night, when active use by phone owners is not likely. CWC uses a single server connected to the Internet, for scheduling jobs on the smart phones and collecting the outputs from the computations [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MicroCast [37] allows closely located smartphones to aggregate the cellular bandwidth, and share downloaded data through WiFi-direct to improve video streaming quality. Recent work, like CWC [38], proposed to harness the computational power of many smartphones to establish a distributed computing platform that offload tasks from costly infrastructures. MobiUS [39] split one video frame between two nearby smartphones to enable better-together viewing experience.…”
Section: Related Workmentioning
confidence: 99%